Influence of residues from bioceramic sealer on the bond interface with universal adhesive in different application modes - Costa, Joatan Lucas de Sousa Gomes; Barros, Antonia Patricia Oliveira [UNESP]; Junior, Adirson Jorge [UNESP]; Gelio, Mariana Bena [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Kuga, Milton Carlos [UNESP] (Wiley, 2024)
This study evaluated the effect on adhesive layer thickness, bond strength, and adhesive failure pattern of the application of universal adhesive (Scotchbond Universal) using either manual or rotary brush in dentin previously impregnated with bioceramic sealer (Sealer Plus BC) using a manual brush, at 24 h and 1 year. Eighty-eight bovine crowns were divided into four groups (n = 22) according to the intervention: (i) use of bioceramic sealer and adhesive application using manual brush, (ii) use of bioceramic sealer and adhesive application using rotary brush, (iii) use of resin sealer and adhesive application using manual brush, and (iv) use of resin sealer and adhesive application using rotary brush. Subsequently, specimens were restored with a composite resin (Filtek Z-250). Adhesive layer thickness was evaluated using confocal microscopy. Bond strength was assessed using the microtensile bond strength test, and adhesive failure pattern was evaluated under a stereomicroscope. Data were analyzed using two-way ANOVA/Tukey tests. Specimens where a rotary brush had been used exhibited lower adhesive layer thickness. Specimens treated with resin sealer and using a manual brush showed lower bond strength values and a higher occurrence of adhesive failures at 24 h and 1 year than specimens treated with bioceramic sealer and using rotary brush for adhesive application.
Keywords: bioceramic sealer; bond strength; protocols; universal adhesive